STUDENTS' PERCEPTIONS OF CAKAP APPLICATION AS A TOOL FOR LEARNING ENGLISH SPEAKING SKILLS - Qomariyah, Siti (ELP (Journal of English Language Pedagogy), 2024)
The effective teaching of English speaking skills requires proficient tools that aid students in exploring vocabulary, forming sentences, and engaging in dialogue. The Cakap application, an educational technology startup from Indonesia, offers a platform focused on two-way online education. This research aims to evaluate student perceptions of using the Cakap application as a tool to enhance English speaking abilities, specifically among students at Arrofi'iyyah Semampir Probolinggo High School. The study employed a case study method involving students from SMAI Ar-Rofi'iyyah in Semampir Village, Kraksaan District, Probolinggo Regency. Data collection methods included observation and, in-depth interviews. The findings indicate that students have a positive perception of the Cakap application, recognizing its potential to improve their English speaking skills. Based on these results, it is recommended that SMAI Ar-Rofi'iyyah integrate the Cakap application into their curriculum to make learning more engaging and effective in enhancing students' English speaking proficiency.